From fear of infection to awareness against stigma: A mixed-methods analysis of discourses on HIV in a parliamentary context - Paule Gonzalez-Recio; Raquel Barba-Sánchez; Édel Granda; Juan-Miguel Guerras; Sara Moreno-García; Alex Iglesias; María José Fuster-RuizdeApodaca; Esther García Expósito; David Palma; María José Belza (PLoS ONE, 2025)
Background and purpose Parliamentary discourse holds significant relevance both socially, due to its impact on stigmatization, and because of its potential legislative consequences. However, despite the persistent stigma surrounding HIV and the numerous regulations that affect people living with HIV, there is a global lack of research on how this topic is addressed in parliamentary debates. This study provides a case analysis from the Madrid Regional Parliament, offering insights that may be applicable to other parliamentary contexts. The principal objective is to analyze the content of HIV-related initiatives in this context, along with its possible relationship to the political parties’ ideology. Methods A mixed-methods quantitative and qualitative study was conducted, including all parliamentary initiatives on HIV from the 12th Legislature of the Madrid Regional Parliament (2021–2023). Subthemes, initiative types, parliamentary groups ideologies, and debate dates were analyzed. Additionally, a Critical Discourse Analysis of the interventions in the plenary sessions was carried out and categorized based on the ideologies of the parliamentary groups, offering insights that may be reflective of broader political discourse trends. Results In the analyzed legislature, 0.09% of all the initiatives addressed HIV. Of these, 83.3% were written, and only 16.7% were presented orally in plenary sessions. Two-thirds focused on prevention, while those concerning access to treatment accounted for 16.7%, and those addressing stigma made up 11.1%. All initiatives were presented by left-wing or center-left parliamentary groups. Right-wing groups discourses centered on fear and the perception of risk, with a strongly stigmatizing rhetoric. In contrast, left and center-left groups emphasized discrimination and stigma as issues and advocated for universal treatment access. Conclusions HIV is minimally addressed in the Madrid Regional Parliament, and when it is, the focus is more on prevention than on addressing the needs of people living with HIV. The study highlights the significant role of political ideology in shaping parliamentary discourse, with stigmatizing rhetoric mainly present in right-wing groups. These findings may offer insights for other legislative bodies where HIV-related stigma and political ideologies intersect.